Integrating Sumbang Duo Baleh Values into Early Childhood Character Education through Interactive Google Sites Media - Warmansyah, Jhoni; Sari, Meliana; Zalzabila, Zakiah; Yulia, Nova; Siregar, Rahayu Yandira; Wiliani, Sherly (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Character education in early childhood is crucial for shaping behavior and morals, especially by integrating local cultural values. This study develops interactive Google Sites media to teach Sumbang Duo Baleh character values to children aged 5-6, using the Research and Development (R&D) method with the 4D model. Validated by education and technology experts, the media achieved a